The encumbrance of institutional investor and board of directors in reducing risk of default for conventional bonds and Sukuk in Malaysia - Noriza Mohd Saad; Mohd Nizal Haniff; Norli Ali (Penerbit Universiti Kebangsaan Malaysia, 2019)
Sukuk yields mimic those of conventional bonds due to having similar features. Sukuk are shariah-compliant securities that offer different structures to those of conventional bonds. Therefore, it is believed that the spreading of yields should also be different. The presence of key institutional investors/owners and certain Board of Directors (BOD) characteristics as highlighted by the Malaysian Code on Corporate Governance (MCCG) may influence the yield to maturity (YTM) of conventional bonds and sukuk. Thus, the main objective of this study is to investigate the relationship between these two yield spreads instruments with corporate governance mechanisms. The data is obtained from firm issuers’ annual reports, the Bondinfo Hub of the Malaysian Central Bank, the Rating Agency Malaysia (RAM), the Malaysian Department of Statistics and Bloomberg databases for the period beginning 2000 to 2014 for 256 and 405 tranches of long-term and medium-term issuances of conventional bonds and sukuk respectively. The most significant findings show that the presence of top-six and other institutional ownerships as corporate governance mechanism proxy insignificantly and significantly reduce yield spreads within the firm revealed by Ordinary Least Square (OLS) and random effects models in long-term and medium-term issuances.